Pengaruh Belajar Daring Terhadap Hasil Belajar Siswa Kelas VIII Pada Mata Pelajaran Al-Qur`An Hadis Di MTS Swasta Darul Arafah Pangkalan Berandan - Nazzli Mahfirah, Kamaliah R, Syarifah (Pusdikra Publishing, 2022)
Online learning in Al-Qur`an Hadith lessons in class VIII of DarulArafah Private MTs PangkalanBerandan, that students study at home through online. The COVID-19 pandemic situation requires students to do learning at home using online methods, requiring students or parents to always be ready with android phones because most teachers send teaching materials and assignments through whatsp or messenger groups, which then collect them or make learning reports via viawhatsapp or messenger, or if possible using email. Obstacles in online learning during the covid-19 pandemic in Al-Qur'an Hadith lessons in class VIII of DarulArafah Private MTs PangkalanBerandan, that during the covid-19 pandemic, student interest in learning decreased drastically, so that in attendance and giving feedback in groups only several students who take part and are active in learning. Ironically, the task given is either in the form of memorization, only some students can do it. Assignments that must be collected are also only a small percentage of students who collect assignments. The effect of online learning during the covid-19 pandemic on the learning outcomes of the Qur'an Hadith in class VIII students of Private MTs DarulArafahPangkalanBerandan is 0.63. Furthermore, to see the level of relationship between the two research variables, it is connected to the data interpretation table in a high relationship, which is between 0.600-0.799. The results of the research test showed a normal distribution pattern, so the regression model met the assumption of normality. As the assumption of a good regression model is to have a normal data distribution or close to normal. And the test results also show that there is an effect of online learning during the COVID-19 pandemic on Al-Qur'an Hadith lessons in class VIII of the Private MTs DarulArafahPangkalanBerandan in a significant condition.